APPLICATION OF CODEIGNITER FRAMEWORK IN DETERMINING THE BEST EMPLOYEES USING THE MOORA METHOD AT THE IBUNDA GENERAL HOSPITAL IN SERANG CITY - Basuki Rakhim Setya Permana; Gagah Dwiki Putra Aryono, Gelard Untirtha Pratama, Ahmad Munawir, Maman Masyhuri (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
This research is based on the need to select the best appropriate employees so that they can maximize employee performance potential. Meanwhile, the process of determining the best employees currently at the "IBUNDA" Maternity Hospital in Serang City is still less than optimal. Based on these problems, a solution was created for a decision support system application to help management assess the overall determination of employees at the "IBUNDA" Nursing Hospital in Serang City easily and quickly. The MOORA (Multi Objective Optimization On The Basis Of Ratio Analysis) method is a decision making method applied to solve problems with complex mathematical calculations. The results of this research are first, in analyzing determining the best employees at the "IBUNDA" public hospital in Serang City, namely by carrying out calculations based on existing criteria so that you can carry out calculations using the MOORA method and get the best results. Second, implementing a decision support system application using the Moora method for selecting the best employees, so that the calculation process can be carried out using this method, and third, in implementing a decision support system application using the MOORA method, implementing the algorithm of this method into the system that will be built to determine employees the best at the "IBUNDA" General Hospital in Serang City.